The birth of the modern mind : the intellectual history of the 17th and 18th centuries - Kors, Alan Charles (Great courses (DVD). Philosophy & intellectual history., 1998)
In twenty-four lectures (each 30 minutes in length), Professor Alan Charles Kors focuses on the revolution of the intellect that seized Europe between 1600 and 1800, a revolution whose lights and shadows are all around us still. This course consolidates and enhances material from two of Professor Kors's earlier courses, The origin of the modern mind and The mind of the enlightenment.